2021
DOI: 10.1109/tse.2019.2904957
|View full text |Cite
|
Sign up to set email alerts
|

Today Was a Good Day: The Daily Life of Software Developers

Abstract: What is a good workday for a software developer? What is a typical workday? We seek to answer these two questions to learn how to make good days typical. Concretely, answering these questions will help to optimize development processes and select tools that increase job satisfaction and productivity. Our work adds to a large body of research on how software developers spend their time. We report the results from 5971 responses of professional developers at Microsoft, who reflected about what made their workday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 100 publications
(139 reference statements)
6
60
0
1
Order By: Relevance
“…Extensive studies performed by Amabile and Kramer support the observation and showed that the single best motivator at work is to empower knowledge workers to make progress, which also increases their happiness [30]. Similarly, recent work suggested that many developers want to gain back control over how they spend their time at work, since work is often very randomized and fragmented by interruptions and meetings [50], [81]. The remainder of this section discusses how self-reflection and various tool support might help developers retain control over their work, make more progress and increase productivity.…”
Section: 4mentioning
confidence: 98%
See 2 more Smart Citations
“…Extensive studies performed by Amabile and Kramer support the observation and showed that the single best motivator at work is to empower knowledge workers to make progress, which also increases their happiness [30]. Similarly, recent work suggested that many developers want to gain back control over how they spend their time at work, since work is often very randomized and fragmented by interruptions and meetings [50], [81]. The remainder of this section discusses how self-reflection and various tool support might help developers retain control over their work, make more progress and increase productivity.…”
Section: 4mentioning
confidence: 98%
“…A related area of research looked into characteristics and work habits of successful developers, some of which developers might consider relevant and important to pursue as goals. Amongst other characteristics, successful developers often share similar attributes, such as striving for productivity and efficiency, being self-aware, asking for and offering help and feedback, constantly learning and self-improving, doing data-driven decisions, and setting challenging goals [1], [2], [14], [35], [49], [50]. Successful developers also manage to find a good balance between focused work and helping or mentoring others [2], [14].…”
Section: Productive Developers' Work Habitsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether software developers' activities have changed during the pandemic, we first compared the time participants reported to have spent on each of the 15 activities with those reported by Meyer et al [16] (first research question). The results are displayed in Figure 1, as well as Tables III and IV.…”
Section: A Changes In Activitiesmentioning
confidence: 99%
“…Observational studies have found that daily planning is an ongoing challenge for knowledge workers such as academics [7] and software developers [9]. Academics, for instance, need to predict how long different tasks will take to complete in order to meet multiple deadlines [7].…”
Section: Introductionmentioning
confidence: 99%